Storm impact on sea surface temperature and chlorophyll a in the Gulf of Mexico and Sargasso Sea based on daily cloud‐free satellite data reconstructions. Issue 23 (14th December 2016) - Shropshire, Taylor; Li, Yizhen; He, Ruoying
Abstract: Upper ocean responses to tropical storms/hurricanes have been extensively studied using satellite observations. However, resolving concurrent sea surface temperature (SST) and chlorophyll a (chl a ) responses along storm tracks remains a major challenge due to extensive cloud coverage in satellite images. Here we produce daily cloud‐free SST and chl a reconstructions based on the Data INterpolating Empirical Orthogonal Function method over a 10 year period (2003–2012) for the Gulf of Mexico and Sargasso Sea regions. Daily reconstructions allow us to characterize and contrast previously obscured subweekly SST and chl a responses to storms in the two main storm‐impacted regions of the Atlantic Ocean. Statistical analyses of daily SST and chl a responses revealed regional differences in the response time as well as the response sensitivity to maximum sustained wind speed and translation speed. This study demonstrates that SST and chl a responses clearly depend on regional ocean conditions and are not as universal as might have been previously suggested. Key Points: Notable regional differences exist in the SST and chl a response to storms Surface bloom responses are associated with different chl a sources in the upper ocean DINEOF is a robust method for analyzing daily storm induced SST and chl a responses